177Lu-PSMA radioligand therapy for prostate cancer - Fendler, Wolfgang; Rahbar, Kambiz; Herrmann, Ken; Kratochwil, Clemens; Eiber, Matthias (Journal of nuclear medicine, 2017)
177Lu-prostate-specific membrane antigen (PSMA) radioligand therapy (RLT) using inhibitors of PSMA is a novel therapeutic option in patients with metastatic castration-resistant prostate cancer. The current literature suggests that this therapy is well tolerated and effective. On the basis of clinical need and current evidence, the therapy is being implemented in a growing number of centers worldwide. Here, we review important aspects of 177Lu-PSMA RLT, including patient stratification, the therapy protocol, concomitant medication, and follow-up, to inform medical staff involved in the RLT and care of patients with metastatic castration-resistant prostate cancer.
Die Zahl 177 ist im Titel hochgestellt
Gesehen am 23.12.2020